A Critical Comparison between Nāma-Rūpa and Cartesian Dualism: Theravāda Buddhist Anattā as a Critique of Descartes’ Cogito Ergo Sum - Fattah, Galuh Nur; Medhacitto, Tri Saputra; Nanda, Gonalagoda (Sekolah Tinggi Filsafat Seminari Pineleng, 2024)
This research article aims to present a critical study on the comparison between the concepts of nāma-rūpa and Cartesian dualism. Nāma-rūpa is a human metaphysical and epistemological concept in Theravāda Buddhism that divides the human self into non-material (nāma) and material (rūpa) aspects. Cartesian dualism, on the other hand, is a human metaphysical concept proposed by René Descartes that also separates the aspects of human self-formation into non-material (res cogitans) and material (res extensa) components. This research article was conducted using the critical comparison method. Despite the same dualistic perspective, this study found that there are significant differences between these two metaphysical concepts. In the context of nāma-rūpa, it is found that the material and non-material aspects of human substance are in a constant state of change due to the influence of Tiḷakkhaṇa (Three Universal Characteristics or Laws) in Theravāda Buddhism. These characteristics or laws encompass Aniccā (Impermanence), Dukkhā (Suffering), and Anattā (Not Self). Therefore, it is impossible to locate the